2023
DOI: 10.26434/chemrxiv-2023-9mbd5
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Controllable Synthesis of Heterofunctionalized Polyethers via an Intramolecular Phosphonium Bisborane Lewis Pair Catalysed Immortal Ring Opening Polymerization

Abstract: A metal-free phosphonium bisborane Lewis pair (PBB-Br) was demonstrated to realize the immortal ring-opening polymerization (iROP) of propylene oxide (PO) under mild conditions with alcohols as chain transfer agents (CTAs). Narrow dispersed poly(propylene oxide) (PPO) with controllable molecular weights predicted from [PO]0/([PBB-Br]0+[CTAs]0) molar ratio were obtained in quantitative conversion. These indicated the iROP feature of PBB-Br-catalysed PO polymerization. The rapid, reversible and quantitative chai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 47 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…In order to identify the nature of the terminal functional group, a lowmolar-mass (5.6 kg/mol) poly(N-tosyl propylene urethane) sample was prepared by copolymerizing TSI and PO with a targeted DP of 25 (Table 1, The above results demonstrated that PBB-Br showed both controlled copolymerization of PO and TSI. Our previous work had shown that PBB-Br could achieve living/controlled polymerization of PO 12,13 and realize the terpolymerization of epoxide, CO 2 and lactide. To show the living anionic propagation site at the chain end in each polymerization, we conducted a sequential addition of monomers to prepare block copolymers.…”
Section: Resultsmentioning
confidence: 99%
“…In order to identify the nature of the terminal functional group, a lowmolar-mass (5.6 kg/mol) poly(N-tosyl propylene urethane) sample was prepared by copolymerizing TSI and PO with a targeted DP of 25 (Table 1, The above results demonstrated that PBB-Br showed both controlled copolymerization of PO and TSI. Our previous work had shown that PBB-Br could achieve living/controlled polymerization of PO 12,13 and realize the terpolymerization of epoxide, CO 2 and lactide. To show the living anionic propagation site at the chain end in each polymerization, we conducted a sequential addition of monomers to prepare block copolymers.…”
Section: Resultsmentioning
confidence: 99%
“…Addition of heterofunctionalized chain-transfer agents led to the formation of functional PPO samples with controllable molecular weights. 241 In 2023, Wu's group made further advancements in exploring other alternative substitutes for ammonium salts. 227 By replacing ammonium salts with a silicon atom, the binary silicon-centered organoboron catalyst exhibited activity that is 7.3 times that of its bifunctional ammonium salt-centered analogue at a low feed [catalyst]/PO molar ratio of 10 000/1, while the corresponding binary alkylborane/ammonium salt systems showed negligible activity.…”
Section: Ring-opening Polymerization Of Epoxidesmentioning
confidence: 99%
“…Organoboron-catalyzed anionic ROP/ROCOP follows an immortal manner in that chain transfer is much faster than propagation. Successful examples demonstrated that phenols, 287 alcohols, 233,241 carboxylic acids, 288 and carboxylate salts 180,286 were all effective chain transfer agents. Therefore, well-defined star and block polymers could be directly synthesized when multifunctional chain transfer agents or macromolecular chain transfer agents 289 were used.…”
Section: Polymers With Different Topology Structuresmentioning
confidence: 99%